Analysis and Design of an Enterprise Campus Area on the Hierarchical Network Infrastructure of STIK Bina Husada Palembang Based on the Cisco Enterprise Model - Wahfiyudin Alkahfi; Edi Surya Negara; Zaid Amin (Jurnal Jaringan Komputer dan Keamanan, 2024)
The utilization of internet-based computer networks has become a fundamental necessity for supporting human activities in the modern era. This is particularly evident in various institutional activities, especially in academic settings such as colleges and schools, which heavily rely on internet network services. However, employing a large network segment with numerous hosts leads to excessive broadcast packet traffic. This issue is further compounded when the network is a flat network that lacks functional grouping for services and devices. To address these challenges, a network migration is necessary: shifting the existing Flat Local Area Network (LAN) to a hierarchical model based on the Cisco Enterprise Model, specifically employing the Enterprise Campus Area approach. This hierarchical design divides the LAN into several network layers, establishing more efficient Broadcast Domains and dedicated service functions, resulting in a system that is more modular and well-managed. The network was designed using the Top-Down method. The resulting design blueprint for the computer network system at STIK Bina Husada Palembang is intended to serve as a reference for future network planning and development.